Educating nurses to deliver optimum care to military veterans and their families. (January 2020) - Finnegan, Alan P; Di Lemma, Lisa; Moorhouse, Ian; Lambe, Rachael E.; Soutter, Ellen M.; Templeman, Jenni; Ridgway, Victoria; Hynes, Celia; Simpson, Robin; McGhee, Stephen
Abstract: The aim of the project was to help prepare the future nursing workforce to provide optimum care for the Armed Forces Community. Structured evidenced-based educational sessions were designed and then delivered at two Universities in England. This educational model included a flipped approach, didactic classroom teaching, blended learning, and information technology. Educational sessions were provided to 468 first year Bachelor of Nursing undergraduate students in 2017 and 2018. A mixed methods evaluation included a quasi-experiential design with pre and post-test data followed by research interviews conducted by student nurses and analysed using a modified Grounded Theory. Post session evaluation demonstrated a significant improvement in students' knowledge. 93% agreed that the training was useful, 95% felt that nurses should be aware of the healthcare needs of the Armed Forces Community, and 89% indicated that the subject matter should be included in the undergraduate curriculum. A qualitative theoretical model was built from four major clusters: the military community; student's identity, clinical engagement, and future practice. These educational sessions are being introduced into a growing number of United Kingdom Universities to create future nursing leaders with a better insight into the large and diverse Armed Forces Community. Highlights: Results indicate knowledge acquisition, high levels of satisfaction, and changes in attitudes. Participants embraced the opportunity to learn the communication skills required for veterans. After the session, a significant majority felt confident in engaging with military veterans. Participants' ruminated on previous clinical practice and advocated a positive change. The initiative is empowering a future nursing workforce to address issues aligned to stigma.